Primary Immunodeficiency Disorders in Children Suffering from Persistent Pneumonia: Experience from A Tertiary Care Hospital - Parveen, Rumana; Kabir, Farhat Lamisa; Masud, Akter Hossan; Sarkar, Probir Kumar; Hoque, Md Mahbubul (Dhaka Shishu (Children) Hospital Journal, 2025)
Background: Persistent pneumonia in children poses a significant challenge to the pediatricians as there are underlying diseases.Primary immunodeficiency disorders (PID) are not uncommon among them. PIDs are always underdiagnosed and underreported from developing countries. Objective: To identify the prevalence and varieties of PID among children with persistent pneumonia. Methods: The crosssectional observational study was conducted atPICU (Paediatric Intensive Care Unit) of Bangladesh Shishu (Children) Hospital & Institute from November, 2019 to October, 2020. Children 2 months to 5 years of age admitted with persistent pneumonia were analyzed to find out the underlying diseases. Results: Among the 49 cases, there were 10 (20.4%) cases of PID. Other underlying diseases were cystic fibrosis 13 (26.5%), congenital heart disease 10 (20.4%), gastroesophageal reflux disease 5 (10.2%), pulmonary tuberculosis 4 (8.2%) and congenital anomaly of respiratory tract 1 (2%). Among the 10 cases of PID, there were 6 patients of SCID, 1 patient of X- linked agammaglobulinemia and 3 patients of selective IgA deficiency. Conclusion: PID was the second most common cause of persistent pneumonia in our study. Among the PID, SCID was the commonest. DS (Child) H J 2023; 39(2): 75-81